Effect of porous structure and morphology of cathode on the degradation of lithium-ion batteries. (1st August 2022) - Lee, Yoon Koo
Abstract: This study investigates the effect of the micromorphology of cathodes with 3D porous structures and geometries on the degradation and electrochemical performance of lithium-ion batteries. Active particle aggregates with different particle diameters and volume fractions are randomly positioned to generate a 3D structure of the cathode in simulation. A physics-based electrochemical model that describes the degradation of the separator, anode, and cathode is developed. Simulation results show that aggregates with a smaller particle radius have a larger surface area, which leads to a higher capacity with a lower concentration gradient but also severe overall degradation. However, with a larger surface area, the volume fraction of the cathode decreases faster, whereas that of the anode decreases slower because of the difference in the fundamental degradation mechanisms of both electrodes. These results indicate that a cathode with a smaller surface area and an anode with a larger surface area are preferred to minimize battery degradation. This morphological information also impacts the diffusivity, which must be carefully optimized for maximizing the capacity and minimizing the degradation. The model developed in this study is expected to be useful to understand degradation mechanisms and to optimize battery design and manufacturing. Highlights: Cathode micromorphology greatly impacts the degradation of lithium-ion batteries. Cathodes with 3D random realistic porous structures and geometries were simulated. A physics-based electrochemical model of cell degradation is developed. Cathode with a smaller and an anode with a larger surface area are preferred. The results help understand degradation mechanisms and optimize battery design.